Nipple-centered Radiate MPR Images of MDCT for Evaluation of Breast Cancer Extent: Correlation with Mammography and Pathologic Specimen - Kunimatsu, Natsuko; Kunimatsu, Akira; Akahane, Masaaki; Morooka, Miyako (The Kitakanto Medical Journal, 2009)
Background & Aims : Evaluation of the extent of breast cancer lesions is important for selecting the appropriate surgical procedure or to determine the surgical margin. We aimed to assess the diagnostic accuracy of nipple-centered radiate multiplanar reconstruction (NRMPR) images using multidetector row helical computed tomography (MDCT), comparing it with conventional mammography. Methods : Our subjects were 26 breast cancer patients with a total of 29 lesions who sequentially received contrast-enhanced MDCT imaging for preoperative evaluation. We measured the maximum diameter of the breast cancer in the direction toward the nipple on NRMPR images and mammography. All data were correlated with histopathological mapping of the specimens. Results : The tumor extent measured on NRMPR images and in pathological examinations ranged from 12.4 to 66.0mm (average, 28.0mm) and 10 to 70mm (average, 27.9mm), respectively. The correlation coefficient of the two measurements was 0.898. On mammography, two lesions were not clearly identified. The correlation coefficient of mammography and pathological measurements was 0.554. Conclusions : The addition of NRMPR images to mammography provides more information to evaluate breast cancer extension toward the nipple. Potentially, it provides a clue for selecting the appropriate surgical procedure or surgical resection margin for breast cancer.